The characteristics of the binding of 12-alpha-[3H]-digoxin to the membranes of intact human erythrocytes: relevance to digoxin therapy. - Ford, A; Aronson, J; Grahame-Smith, D; Rose, J (1979)
1 The characteristics of the binding of 12-alpha-[3H]-digoxin to the membranes of intact human erythrocytes are described. 2 Only one class of binding site can be demonstrated. Binding is time- and temperature-dependent, saturable and slowly reversible; it is inhibited by other cardiac glycosides and by potassium. 3 Pre-incubation with unlabelled digoxin reduces the subsequent binding of 12-alpha-[3H]-digoxin in stoichiometric fashion. 4 The possible application of the measurement of the binding of 12-alpha-[3H]-digoxin to the study of biochemical pharmacological events occurring during digoxin therapy is discussed.